The standardisation of uveitis nomenclature (SUN) project. (23rd October 2022) - Jabs, Douglas A.; McCluskey, Peter; Palestine, Alan G.; Thorne, Jennifer E.; The Standardization of Uveitis Nomenclature (SUN) Working Group
Abstract: The uveitides are a collection of over 30 diseases characterised by intraocular inflammation. Previous work demonstrated that the agreement among uveitis experts on diagnosis was modest at best with some pairs of experts having chance alone agreement on selected diseases. The Standardisation of Uveitis Nomenclature (SUN) is a17‐year collaboration among experts in uveitis, ocular image grading, informatics, and machine learning to improve clinical and translational uveitis research. The SUN "Developing Classification Criteria for the Uveitides" project used a rigorous, multi‐phase approach to develop classification criteria for 25 of the most common uveitic diseases. The project's phases were: (1) informatics; (2) case collection; (3) case selection; (4) machine learning; and (5) consensus review and publication. The results were classification criteria with a high degree of accuracy (93.3%–99.3% depending on anatomic class of the uveitis), the goal of which is to form the basis for future uveitis research.